1997
DOI: 10.1128/jvi.71.7.5487-5494.1997
|View full text |Cite
|
Sign up to set email alerts
|

Formation of intracellular particles by hepatitis B virus large surface protein

Abstract: Hepatitis B virus small surface protein is synthesized as a transmembrane protein of the rough endoplasmic reticulum (RER) and then buds into the lumen in the form of subviral particles that are secreted. The closely related large surface protein is also targeted to the RER but is retained in a pre-Golgi compartment and cannot be secreted. It has been assumed that the large surface protein remains as a transmembrane RER protein and hence cannot form particles, possibly because of binding to a host factor on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…A recent study demonstrated that LHBs itself can form 20-nm particles which are retained in a post-rough endoplasmic reticulum compartment, possibly by interacting with calnexin and other regulatory endoplasmic reticulum proteins. 49 Our analyses excluded the possibility that LHBs inhibits the secretion of IL-2 and GM-CSF. The effects of LHBs on the immune response augmenting properties of IL-2 and GM-CSF in vivo, therefore, were not related to the inhibition of their secretion from the cell by LHBs as demonstrated by in vitro transfection experiments.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study demonstrated that LHBs itself can form 20-nm particles which are retained in a post-rough endoplasmic reticulum compartment, possibly by interacting with calnexin and other regulatory endoplasmic reticulum proteins. 49 Our analyses excluded the possibility that LHBs inhibits the secretion of IL-2 and GM-CSF. The effects of LHBs on the immune response augmenting properties of IL-2 and GM-CSF in vivo, therefore, were not related to the inhibition of their secretion from the cell by LHBs as demonstrated by in vitro transfection experiments.…”
Section: Discussionmentioning
confidence: 96%
“…These results indicated that both pre-S mutant constructs lead to retention of large S-protein at the ER. Earlier experiments performed by Xu et al 38 demonstrated that the large S-protein colocalizes with calnexin, a luminar protein of the ER that might prevent the large S-protein from secretion. They also showed that the mutated S-proteins are still capable of building globular HBsAg particles.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a recent study, the L protein alone was found to form intravesicular 20-nm spherical particles identical to the S and M protein particles but retained in intracellular compartments by calnexin. 17 Nevertheless, the so-called ground-glass appearance of the hepatocytes in chronic HBV infection seems to be caused by the intracellular accumulation of L-protein-rich filaments. This intracellular accumulation is seen in patients in late phases of chronic HBV infection, especially at the phase of cirrhosis, when a high level of intracellular expression of HBV surface proteins is associated with a low level of serum HBV surface proteins.…”
Section: Discussionmentioning
confidence: 99%